TESTING CHEMICAL PROPERTIES ON WET NOODLES HAS BEEN SUSPECTED WITH PLUSH FLOUR (Rastrelliger sp.) - Liean A. Ntau; Rahma Labatjo; Fitri Yani Arbie (Universitas Negeri Gorontalo, 2022)
Noodles are widely consumed and favored by almost all Indonesian people because noodles have various advantages, including distinctive taste, texture, shape, relatively affordable prices, and ease of processing. Noodles can be modified or substituted with mackerel flour to increase the nutritional value of wet noodles. Mackerel is a freshwater fish containing omega 3 and omega 6, which can prevent disease by educating the brain. This study aimed to determine and analyze the chemical properties of wet noodles, which have substituted with mackerel (Rastrelliger sp) flour. The research design used was True Experimental Design Posttest-Only Control Design Posttest-Only Control Design with Completely Randomized Design (CRD). Parameters measured in this study were data on carbohydrate content, protein content, fat content, iron content. The results showed that the carbohydrate content of wet noodles ranged from 56.37% - 59, 87%, protein content of wet noodles ranged from 11.28% - 16.45, the fat content of wet noodles ranged from 4.637% - 7.462%, the iron content of noodles wet ranged from 3.197% - 6.39%